Domain-Dependent Heuristics and Tie-Breakers: Topics in Automated Planning - Corrêa, Augusto B.; Pereira, André G.; Ritt, Marcus (Anais do Concurso de Trabalhos de Iniciação Científica da SBC (CTIC-SBC); 2018: Anais do XXXVII Concurso de Trabalhos de Iniciação Científica da SBC, 2018)
Automated planning is an important general problem solving technique in Artificial Intelligence. Given an initial state, a goal and a set of operators, we want to find a sequence of operators leading us to the goal. What makes planning interesting is that it can model different domains into planning tasks and solve them using a single method. In this work, we approach two different topics in planning. First, we study heuristics for the airport ground traffic problem and propose new heuristics that are better than any other known method. In the second part, we study tie-breakers for the A∗ search algorithm. We propose a new tie-breaking method that is proved to be the best possible and also show that our methods solve more instances than previous methods in literature.